Policy Framework for Sustainable Real Estate Markets - United Nations (United Nations, 2019)
The UNECE Real Estate Market Advisory Group (REM) is a group of real estate experts who advise the Committee on Urban Development, Housing and Land Management on sustainable real estate markets, working to identify specific measures to strengthen a country’s real estate market in a manner that would contribute to economic growth and sustainable development. In 2010, the REM Advisory Group published the “Policy Framework for Sustainable Real Estate Markets”, a tool that would help guide the member States to create sustainable real estate markets. However, the emergence of key international agreements, such as the 2030 Agenda for Sustainable Development, the Geneva UN Charter on Sustainable Housing, the New Urban Agenda, the Paris Agreement, and the Basel III Agreement, have led to the establishment of new global and regional policy frameworks for future activities on sustainable urban development at all levels. In response to the request of the Committee to update the Policy Framework to reflect the emergence of such key agreements, the REM Advisory Group produced the current publication, which now also includes updates on the issues such as urbanization, migration and mobility flows, technology and innovation, the growth of emerging markets and asset competition, the change in housing demand oriented towards green buildings and new designs, energy consumption and climate change, and other relevant phenomena. Moreover, this version of the Policy Framework for Sustainable Real Estate Markets maintains that, contrary to the widespread belief that finance and real estate sectors have negative impact on sustainability, they can actually contribute to the achievement of Sustainable Development Goals with the implementation of effective and compatible principles. In particular, this publication shows that these principles can be incorporated by national, local and municipal governments and applied to various forms of real estate.